Occupational Health and Safety Risk Analysis Using The HAZOP Method at UD Kerupuk Mamak Kito - Ardeline, Mela; Lasmita, Revi (Journal of Engineering Science and Technology Management (JES-TM), 2025)
Occupational Health and Safety (OHS) is an approach designed to prevent workplace accidents that may cause death, injury, or disability. If potential hazards in the workplace are not adequately identified and managed, they can lead to fatigue, musculoskeletal disorders, injuries, or serious accidents. Due to the high-risk nature of its production processes and the lack of ergonomic considerations, the kerupuk processing industry at UD Mamak Kito must pay greater attention to Health, Safety, and Environment (HSE). One method to support OHS implementation is the HAZOP (Hazard and Operability Study) method, which systematically identifies potential hazards in the workplace. The study identified ten high-risk conditions, primarily associated with the use of personal protective equipment (PPE), ergonomics, and exposure to high heat or hot oil. Six moderate-risk conditions were also found, including failure to use PPE and minor environmental hazards. Low-risk factors, including minor cuts and slippery surfaces, were additionally observed. Based on these findings, recommended improvements include enhancing workplace conditions and promoting safer work practices to reduce the risk of accidents and occupational health problems.